Core–shell nanoparticles used in drug delivery-microfluidics: a review. Issue 31 (13th May 2020) - Mahdavi, Zahra; Rezvani, Hamed; Keshavarz Moraveji, Mostafa
Abstract : Developments in the fields of lab-on-a-chip and microfluidic technology have benefited nanomaterial production processes due to fluid miniaturization. Abstract : Developments in the fields of lab-on-a-chip and microfluidic technology have benefited nanomaterial production processes due to fluid miniaturization. The ability to acquire, manage, create, and modify structures on a nanoscale is of great interest in scientific and technological fields. Recently, more attention has been paid to the production of core–shell nanomaterials because of their use in various fields, such as drug delivery. Heterostructured nanomaterials have more reliable performance than the individual core or shell materials. Nanoparticle synthesis is a complex process; therefore, various techniques exist for the production of different types of nanoparticles. Among these techniques, microfluidic methods are unique and reliable routes, which can be used to produce nanoparticles for drug delivery applications.